THE PERFORMANCE OF RED RICE OF ENSALANG TYPE ON RICE LAND - 1, Farendra (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACTPerformance studies of rice were considered very essential in order to understand the description of the characters possessed by red rice types. This study aims to determine the morphological and agronomic characters of Tabah red rice type qualitatively and quantitatively based on the Guide to Rice Crop Characterization and Evaluation Systems (Ministry of Agriculture, 2003). The research was carried out on paddy fields owned by Sungai Kakap Seed Development Board Plant. The results showed that the agronomic character of Tabah red rice has the ability to medium breed (12.96), plant height in the vegetative phase maximum 125.85 cm classified as medium, panicle and neck panicle out thoroughly, grain fertility 83.47% classified as fertile, Plant age of 152 days is classified as deep, and the yield is 8.14 tons / ha. Morphological characters were seedling height 38.17 cm, leaf length 58.56 cm classified as medium, leaf width 1.39 cm classified as wide, surface of hairy leaves and rough, 37.5 ° leaf angles classified as upright, leaf angle 45 ° classified as medium, light green leaf neck, white leaf ears colorless, golden yellow leaf book, light green leaves, green leaf midrib, 1.8 cm long tongue leaf , the leaf tongue is white (Yellow-Green Group 145 A), the tongue shape is 2-cleft, the stem angle is 30 ° is medium, the stem is yellow gold (Yellow-Green Group 151 D), the panicle is 27.43 cm, panicle type is classified as medium and open, panicle is drooping, seed length is 9.55 mm classified as very long, seed width 3,81 mm, seed thickness 1,86 mm, and weight of 100 grains 2.17 grams with moisture content of 13.6 %. Keywords: agronomy, red rice, characterization, morphology, Ensalang rice type.